2021
DOI: 10.3390/insects12050443
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Models Predict Invasive Bee Habitat Suitability Will Expand under Future Climate Scenarios in Hawai’i

Abstract: Climate change is predicted to increase the risk of biological invasions by increasing the availability of climatically suitable regions for invasive species. Endemic species on oceanic islands are particularly sensitive to the impact of invasive species due to increased competition for shared resources and disease spread. In our study, we used an ensemble of species distribution models (SDM) to predict habitat suitability for invasive bees under current and future climate scenarios in Hawai’i. SDMs projected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Range extensions on similarly large scales have been discovered in Anthophorula micheneri (Timberlake, 1948) (Sellers and McCarthy 2015), Diadasia ochracea (Cockerell, 1903) (Gibbs, unpublished data), Lasioglossum semicaeruleum (Cockerell, 1895) (Scarpulla and Droege, unpublished data), and several introduced Hawaiian bees, including four L. (Dialictus): L. helianthi, L. impavidum (Sandhouse, 1924), L. microlepoides (Ellis, 1914, and L. puteulanum Gibbs, 2009(Magnacca et al 2013Tabor and Koch 2021). It is therefore plausible that the Manitoba specimen is truly conspecific with the American and Mexican specimens and not a separate, cryptic species.…”
Section: Figure 12mentioning
confidence: 71%
“…Range extensions on similarly large scales have been discovered in Anthophorula micheneri (Timberlake, 1948) (Sellers and McCarthy 2015), Diadasia ochracea (Cockerell, 1903) (Gibbs, unpublished data), Lasioglossum semicaeruleum (Cockerell, 1895) (Scarpulla and Droege, unpublished data), and several introduced Hawaiian bees, including four L. (Dialictus): L. helianthi, L. impavidum (Sandhouse, 1924), L. microlepoides (Ellis, 1914, and L. puteulanum Gibbs, 2009(Magnacca et al 2013Tabor and Koch 2021). It is therefore plausible that the Manitoba specimen is truly conspecific with the American and Mexican specimens and not a separate, cryptic species.…”
Section: Figure 12mentioning
confidence: 71%
“…Previous studies have revealed the superior predictive performance of EM over a single SDM, and single model uncertainty can be avoided or reduced by EM [ 40 , 41 ]. For instance, some studies on the prediction of the distribution pattern of Vespa velutina in the Mediterranean island regions [ 42 ], estimating the global invasion risk for Hemiculter leucisculus [ 43 ] and predicting the habitat suitability for the invasive bee in Hawai’i [ 44 ], indicated that the predictions using an EM were more reliable than those using a single SDM. We also assessed niche dynamics during the global invasion process and significant variables affecting the global distribution pattern of P. semipunctata .…”
Section: Discussionmentioning
confidence: 99%
“…Lasioglossum puteulanum was previously only known from the southeastern United States. It was first reported from Hawaii by Tabor & Koch (2021), but has evidently existed there and gone undetected for some time previously. The specimens of L. helianthi from Magnacca et al (2013) were examined and found to be a mixed series including some L. puteulanum, and a successful DNA barcode from one of these specimens confirmed the identification.…”
Section: Commentsmentioning
confidence: 99%
“…This group is extremely widespread in the Western Hemisphere, ranging throughout most of North America (only absent from northern Canada) (Gardner & Gibbs 2022) and western South America from Colombia to Argentina and Chile (Engel 2000;unpublished data). It occurs even on remote islands including Hawaii (Tabor & Koch 2021), the Greater Antilles (Gibbs 2018b), Isla Socorro (unpublished data), and the Archipiélago de Juan Fernández (Engel 2000). This suggests a great dispersal ability, although the species occurring in Hawaii are known to be non-native there and may have been introduced by humans (Magnacca et al 2013).…”
Section: Introductionmentioning
confidence: 99%